Implementation of the Ummi Method in Increasing Interest in Learning the Qur'an Among Students at the Riyadlul Jannah Islamic Boarding School TPQ - Zakiyyah Rahma Agustin; Muhammad Wildan Shohib (MASI Mandiri Edukasi, 2026)
This study aims to describe the implementation of the Ummi Method to increase students' interest and enthusiasm in learning the Qur'an at the TPQ Riyadlul Jannah Islamic Boarding School in Ngreni, Simo, Boyolali. This study uses a qualitative, phenomenological approach, with data collected through observation, in-depth interviews, and document analysis. Data analysis was conducted using the stages of data reduction, data presentation, and conclusion drawing to comprehensively understand the learning process. The results showed that the Ummi Method improved students' reading quality, motivation, and confidence through structured, interactive, and enjoyable learning. Students experienced significant progress in pronunciation accuracy, recitation fluency, and memorization thanks to the memorization target system, reading and listening exercises, and munaqosyah activities. The implementation of the Ummi Method consisted of seven main stages: opening, apperception, concept planting, concept understanding, skill training, evaluation, and closing. In addition, the application of the classical-individual model, the mapping of abilities through initial screening, and the development of teacher quality through tahsin, tashih, certification, and routine evaluation further strengthen the effectiveness of this method. Thus, the Ummi Method has proven to be an effective strategy for teaching the Qur'an, increasing students' interest in learning, reading quality, and discipline.